2018
DOI: 10.2298/pif1801009m
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic potential of Bacillus spp. isolates against bacterial pathogens of tomato and fungal pathogen of pepper

Abstract: In vitro antagonistic potential of eleven isolates of Bacillus spp. against two phytopathogenic bacteria and one fungus was tested in order to identify potential biocontrol agents in vegetable crops. The Bacillus spp. isolates demonstrated different levels of antagonistic effect against the tested pathogenic microorganisms. Data in the study proved Xanthomonas vesicatoria to be more sensitive to Bacillus spp. strains than Clavibacter michiganensis subsp. michiganensis. Ten B. subtilis strains induced growth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
(31 reference statements)
1
6
0
1
Order By: Relevance
“…This type of knowledge might be important for future industrial application purposes of B.c-A, because it is important to search for cheaper culture mediums, in order to diminish costs of large-scale production of PGPBs. Moreover, it has been reported that strains of B. subtilis and Pseudomonas sp display antagonistic activity in vitro and in vivo , respectively, against Cmm and the bacterial canker in tomato [ 24 ] and [ 25 ]. To our knowledge, the results of the present work are the first report showing that a strain of Bacillus cereus (as B.c-A) displays in vitro and in vivo antagonistic activity against Cmm and the canker disease provoked by this pathogen in tomato.…”
Section: Discussionmentioning
confidence: 99%
“…This type of knowledge might be important for future industrial application purposes of B.c-A, because it is important to search for cheaper culture mediums, in order to diminish costs of large-scale production of PGPBs. Moreover, it has been reported that strains of B. subtilis and Pseudomonas sp display antagonistic activity in vitro and in vivo , respectively, against Cmm and the bacterial canker in tomato [ 24 ] and [ 25 ]. To our knowledge, the results of the present work are the first report showing that a strain of Bacillus cereus (as B.c-A) displays in vitro and in vivo antagonistic activity against Cmm and the canker disease provoked by this pathogen in tomato.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the sequence identity of > 99% (considered to belong to the same species), the isolates were assigned to 20 groups spanning 18 genera and five phyla. Previous reports 35 , 36 showed that closely related strains (including those shared > 99.2% of 16S rRNA gene similarity 36 ) similarly exhibited antagonistic activities. In this study, a representative strain was selected from each group assuming that strains of each group exhibit similar antagonistic characteristics.…”
Section: Resultsmentioning
confidence: 82%
“…The production of siderophores 10 , bacteriocins 41 , lipoprotein 17 , hydrogen peroxide 35 , and blocking quorum-sensing 16 are considered as the mechanisms underlying the antagonistic ability of bacteria. Among these, GL7 produced siderophores, whereas OX14 was also weakly positive.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that P. polymyxa ( Zhang et al, 2018 ), Bacillus sp. ( Milijasevic-Marcic et al, 2018 ), and Streptomyces sp. ( Olanrewaju and Babalola, 2019 ) are disease-inhibiting bacteria.…”
Section: Introductionmentioning
confidence: 99%